Perancangan Sistem Informasi Rekrutmen Karyawan Dengan Metode RUP - Leli Yanah; Sri Hardani; Suharyanto Suharyanto; Endang Muthia (Journal of Information System, Applied, Management, Accounting and Research, 2022)
PT. Trikarya Cemerlang is one of the outsourcing companies whose business filed are provide janitor, security officers and others. PT. Trikarya Cemerlang has employee recruitment information system that is still manual or has not computerized yet. This system lack of effectiveness and efficiency. So we need a new employee recruitment information system design by using computerized system. By using web-based design new employee recruitment information system, hope it can help the company to recruit new employee, and also help the prospective employees to apply their application letter to the company. This research implement Rational Unified Process (RUP) methodology to develop the application. For the system design method is using the Object Oriented Analysis and Design method with UML diagram such as use case diagrams, activity diagrams, and sequence diagrams. As a result of the system, users easy to manage data, recruit employees, and process complete reports.